PELUANG PENGEMBANGAN AGROINDUSTRI BERBASIS PERIKANAN LAUT DI DUSUN PAYANGAN DESA SUMBEREJO KECAMATAN AMBULU KABUPATEN JEMBER - Syamsul Hadi; Nurul Fathiyah Fauzi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2016)
ABSTRACTThe  development  of  agro-industries  through  the  development  of  domestic  industry  based fisheries  in  the  Payangan  hamlet  Sumberejo  District  of  Ambulu  Jember  faced  with  various problems that started from the central issue is the level of knowledge and skills  is relatively low, the ownership of venture capital is relatively limited, the production activities as individuals not groups, access  difficult  commercial  lending  and  access  to  technology  is  also  difficult.  These  conditions resulted  in  labor  productivity  and  production  quality  is  low.  The  purpose  of  this  study  were:  1) Knowing  the  agro-industry  development  opportunities  based  marine  fisheries;  2)  Analyze  the added value of the fish catch if processed further; and 3) to analyze the socio-economic factors that affect  the  chances  of  developing  agro-industries  based  marine  fisheries.  The  method  used  is descriptive quantitative and qualitative survey techniques. Types of populations in this study were fishermen and craftsmen, artisans and fishermen of each sampl e taken as many as 10, 11 and 9 of the  techniques  of  simple  random  sampling  and  quota  sampling,  while  the  data  collection techniques  used  depth  Interview.  Analysis  of  the  data  used  to  answer  the  purpose  of  the  first, second  and  third  use  analysis  tools  respective  R  /  C  Ratio,  Value-added  models  Hayami  and probability  cumulative  logit  model.  The  results  of  this  study  concluded:  1)  Opportunities-based agro-industrial development of marine fish in the study area is wide open (R / C = 4.61); 2) Activity based  agro-industry  marine  fish  that  includes  pemindangan,  fogging  and  making  shrimp  paste provide  added  value  as  much  as  Rp  43,672.02  per  kg  per  production  process;  and  3) Simultaneously  five  independent  variables  significantly  affect  the  chances  of  developing  agroindustry  and  the  partial  factor  significant  business  experience,  whereas  other  estimators  factors had no significant effect.Keywords: added value, agro-industry, development opportunities ABSTRAK Pengembangan  agroindustri  melalui  pengembangan  industri  rumah  tangga  yang  berbasis perikanan  di  Dusun  Payangan  Desa  Sumberejo  Kecamatan  Ambulu  Kabupaten  Jember dihadapkan pada berbagai masalah  yang  dimulai dari masalah pokok  yaitu tingkat pengetahuan dan ketrrampilan relatif rendah, kepemilikan modal usaha relatif terbatas, kegiatan produksi secara perseorangan tidak berkelompok, akses pinjaman modal usaha sulit dan akses teknologi juga sulit. Kondisi ini mengakibatkan produktivitas tenaga kerja dan kualitas produksi menjadi rendah. Tujuan penelitian ini adalah: 1) Mengidentifikasi peluang pengembangan agroindustri berbasis perikanan laut;   2)  Menganalisis  nilai  tambah  hasil  tangkapan  dalam  bentuk  olahan;   dan  3)  Menganalisis faktor  sosial  ekonomi  yang  mempengaruhi  peluang  pengembangan  agroindustri  berbasis perikanan  laut.  Metode penelitian yang digunakan adalah deskriptif-kuantitatif dan kualitatif melalui teknik  survei.  Target  responden  adalah  nelayan  sekaligus  pengrajin,  pengrajin  dan  nelayan, sebanyak masing-masing 10, 11 dan 9 orang melalui teknik  simple  random sampling  dan quota sampling.   Teknik  pengumpulan  data  digunakan  depth  Interview.  Analisis  data  yang  digunakan untuk  menjawab  tujuan  pertama,  kedua  dan  ketiga  digunakan  alat  analisis  masing-masing  R/C Ratio, nilai tambah model Hayami dan probabilitas komulatif Model Logit. Adapun hasil penelitian ini menyimpulkan: 1)  Peluang pengembangan agroindustri berbasis ikan laut di daerah penelitian sangat  terbuka  lebar  (R/C  =  4,61);  2)  Kegiatan  agroindustri  berbasis  ikan  laut  yang  meliputi pemindangan,  pengasapan  dan  pembuatan  terasi  memberikan  nilai  tambah  sebanyak  Rp43.672,02 per kg per proses produksi; dan 3)  Secara simultan kelima variabel bebas berpengaruh nyata  terhadap  peluang  pengembangan  agroindustri  dan  secara  parsial  faktor  pengalaman berusaha berpengaruh nyata, sedangkan faktor penduga lainnya  tidak berpengaruh nyata.Kata kunci: nilai tambah, agroindustri, peluang pengembangan